Toplum Temelli Turizm: Lavanta Kokulu Köy Örneği - Yordam, Selda; Düşmezkalender, Ebru (Turk Turizm Arastirmalari Dergisi, 2019)
Community-based tourism (CBT) aims to have the local communities have a say in the decisions taken about tourism, to participate in tourism, to benefit from tourism incomes, and to protect local cultures. In this study, it is aimed to set forth perceptions of the local communities toward community-based tourism. Kuyucak village, where the ‘Lavender Scented Village’ Project was realized, has been designated as the research area. Convenience sampling method has been used in the research, data has been collected via survey, and 152 people were reached. For the purpose of research, frequency analysis, factor analysis, Mann-Whitney U and Kruskall Wallis tests have been used while analyzing the data. In the light of the research, it has been observed that CBT’s environment protection sub-dimension differs accordingly to age. In addition, general community-based tourism perception and CBT’s socio-economic sub-dimension has been seen to show significant differences according to the level of income. The obtained data is expected to be enlightening for future studies.
Keywords: 8. Economic growth; 11. Sustainability; 12. Responsible consumption